Cluster based analysis of student performance in academic work at Wilgamuwa area in Sri Lanka - Goonathilake, M. A. M.; Santhushti, W. M. S.; Wijayakulasooriya, J. V. (International Conference on Child Protection 2025, University of Kelaniya, Sri Lanka., 2025)
Background: School dropout rates in Sri Lanka are significantly higher in rural areas due to widespread socioeconomic disparities. In the Wilgamuwa region, these educational challenges are intensified by the high prevalence of chronic kidney disease of Unknown Etiology (CKDu), which adds additional burdens on students and families. This study aims to classify students into clusters based on academic performance and related factors to identify targeted interventions which can improve educational outcomes. Method: Data were collected from 150 students in grades 9 to 11 in the Wilgamuwa area from December to February 2025 by using a structured survey. The survey evaluated five key domains: School Background, Family Background, Social and Emotional well-being, Economic challenges, and Academic performance. Responses were measured on a 1-5 scale question type and treated as interval data. Students were grouped into clusters using k-means clustering, and box plot analysis was used to compare differences among clusters. Results: Three distinct student clusters emerged: Cluster 1 - Students benefit from advanced coursework and enrichment programs. Cluster 2 - Students require targeted academic support and motivation. Cluster 3 Students need personalized intervention, including financial and socio-emotional support. Economic challenges were particularly significant among older students, where financial stress hurt academic performance. Additionally, 15-year-old students showed higher levels of social and emotional difficulties compared to their younger peers. School-related factors, such as infrastructure and teaching quality, also influenced academic outcomes across all clusters. Conclusions: A one-size-fits-all approach to education is ineffective in this context. The study recommends three tailored intervention programs aligned with the needs of each student cluster, including financial support, mental health services, and differentiated teaching strategies. Future research should explore additional socioeconomic and psychological factors to guide education policy in rural communities.
Keywords: Student performance; clustering analysis; rural education; socioeconomic factors; CKDu